2023
DOI: 10.1038/s41564-022-01293-8
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth is associated with xenobiotics and predicted by the vaginal metabolome

Abstract: Spontaneous preterm birth (sPTB) is a leading cause of maternal and neonatal morbidity and mortality, yet its prevention and early risk stratification are limited. Previous investigations have suggested that vaginal microbes and metabolites may be implicated in sPTB. Here we performed untargeted metabolomics on 232 second-trimester vaginal samples, 80 from pregnancies ending preterm. We find multiple associations between vaginal metabolites and subsequent preterm birth, and propose that several of these metabo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 112 publications
2
34
0
Order By: Relevance
“…This result suggests that the more diverse gene pool in G. swidsinskii (PG044) detected in sPTB may be associated with adaptation to drugs present in the environment. This may be consistent with our recent finding that xenobiotics detected in the vaginal environment are strongly associated with sPTB 34 .…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This result suggests that the more diverse gene pool in G. swidsinskii (PG044) detected in sPTB may be associated with adaptation to drugs present in the environment. This may be consistent with our recent finding that xenobiotics detected in the vaginal environment are strongly associated with sPTB 34 .…”
Section: Resultssupporting
confidence: 93%
“…Notably, we found that sPTB-associated purifying selection is particularly strong on genes involved in lipid transportation and metabolism. This is consistent with previous identification of lipid metabolites (e.g., monoacylglycerols and sphingolipids) as signatures of sPTB 34,64,65 . Whether this stronger purifying selection targeting lipid transportation and metabolisms in pregnancy that ended preterm leads to changes in the concentrations of lipid metabolites however requires further experimental testing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Major communication between host and gut microbiota takes place through the metabolites, such as acetate, butyrate, and propionate, and via the microbiota composition modulating metabolism processes. 783 786 Gut microbiota acts as an “invisible organ” and produces active metabolites via their receptor signal to regulate the host metabolism that affects systemic health, and plays a variety of effects on the host from shaping gut structure and function to the modulation of the host status. The increasing evidence showing that gut environment disorder could affect various organs lead to metabolic diseases.…”
Section: Metabolic Homeostasis and Gut Microbiotamentioning
confidence: 99%